1976
DOI: 10.1021/ja00439a600
|View full text |Cite
|
Sign up to set email alerts
|

Stable Carbocations. 198. Formation of Allyl Cations via Protonation of Alkynes in Magic Acid Solution. Evidence for 1,2-Hydrogen and Alkyl Shifts in the Intermediate Vinyl Cations

Abstract: A series of 12 alkynes has been protonated with FSO3H-SbFs (magic acid) in SO2 or S02CIF solution under stable ion conditions. Whereas the formation of oligomeric products was observed at -78 OC, allyl cations were formed in high yields at higher temperatures. In many cases this way of preparing allyl cations is superior to other methods. While alkynes, which are branched in the a position to the triple bond, underwent rearrangements to allyl cations after protonation in SO2 at -20 O C , the corresponding reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 19 publications
2
12
0
1
Order By: Relevance
“…1B) (21, 22). In this reaction, and in analogous reports from Olah and Mayr (23) and Caple and others (24), this unusual C–C bond–forming process was rationalized via a carbocation rebound mechanism. Here the vinyl cation 5 is quenched via 1,5-hydride shift, and the neutralized alkene (6) attacks the newly formed alkyl carbocation.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…1B) (21, 22). In this reaction, and in analogous reports from Olah and Mayr (23) and Caple and others (24), this unusual C–C bond–forming process was rationalized via a carbocation rebound mechanism. Here the vinyl cation 5 is quenched via 1,5-hydride shift, and the neutralized alkene (6) attacks the newly formed alkyl carbocation.…”
supporting
confidence: 69%
“…Subjection of butenyl triflate 21 to the reaction conditions led to high-yielding reductive alkylation of cyclohexane, providing 2-cyclohexylbutane (22) in 85% yield (Table 2, entry 1). We found that the treatment of a cyclohexane solution of but-1-en-2-yl triflate (23) with 2 mol % of [Ph 3 C] + [HCB 11 Cl 11 ] − and 1.5 equivalents of triethylsilane led to formation of a 1:1 mixture of 1-cyclohexylbutane (24) and 2-cyclohexylbutane (22) (Table 2, entry 2). Moreover, use of a 1:1 mixture of C 6 D 12 :C 6 H 12 in this system led to exclusive formation of D 12 and D 0 isomers, without any detectable amount of crossover products (that is, C 10 H 8+ n D 12- n or C 10 H 20– n D n , n ≠ 0) that would be expected in a stepwise process (fig.…”
Section: Reactivity Of Acyclic Vinyl Triflatesmentioning
confidence: 99%
“…Additionally due to the possibility of increased resonance stabilization in the cation, allyl, benzyl, and benzoyl substrates typically tend to favor stepwise unimolecular S N 1 (dissociative) reactions [29,33,51,52,6265]. An allyl cation with two resonance contributors is shown to have approximately the same stability as a secondary alkyl cation [66]. On the other hand reactivity at an sp 2 carbon of vinyl substrates is dependent on whether the substrate is activated or unactivated, for alkyl-substituted vinyl triflates are shown to solvolyze through ion-pair mechanisms where nucleophilic solvation is important in substrates where the β hydrogen is trans to the leaving group [6673].…”
Section: Introductionmentioning
confidence: 99%
“…To assess the vinyl cation character of intermediate C/C',w e decided to investigate its ability to promote CÀHi nsertion. Indeed, as experimentally observed [5] and then rationalized by DFT studies, [37] vinyl cationsp ossess ac arbenic reactivity [38] resulting in their insertion into inert CÀHb onds. We thus prepared substrate 1v bearing an isopropyl chain ands ubmitted it to cycloisomerization in the presence of 5mol %o fB rønsted acid catalyst 7a as model catalyst (Scheme 3).…”
mentioning
confidence: 58%